Examining trend and synergistic development of China’s ‘new three’ industries, China-Europe trade, and China Railway Express - Yu Lin; Fuyu Lai; Xuefei Liu; Zhenguo Shi; Dongxu Chen (All Earth)
This paper investigates the synergistic development of China’s ‘new three’ industries, referring to electric vehicles, lithium batteries, and solar batteries, the China Railway Express (CR-Express), and the China-Europe trade. Using panel data from 2017 to 2023, we first disclose the development trend of ‘new three’ industries and China-Europe trade. Secondly, the synergistic relationship among ‘new three’ industries, and the synergistic relationship CR-Express and China-Europe trade are demonstrated form the spatiotemporal correlations perspective based on correlation and regression analysis. Thirdly, the synergistic development of China’s ‘new three’ industries and the CR-Express trade is evaluated based on qualitative and quantitative analysis method. Our findings show: 1) China’s ‘new three’ industries show an upward export trend to Europe, aligning with the development of the CR-Express; 2) The correlation between the industries exports shows strong interconnections, particularly between electric vehicles and lithium batteries (0.988). Besides, the CR-Express’s export correlation with China-Europe exports is 0.952, demonstrating its role in enhancing trade; 3) A sensitivity analysis of electric vehicle exports via CR-Express suggests the importance of timing for optimising access to European markets. The results underscore how transportation infrastructure and industrial growth can reinforce each other, reshaping trade patterns and offering valuable guidance for policymakers and stakeholders.